Search the dark eaudiobook - Todd, Charles (Inspector Ian Rutledge Mystery, 2015)
Dorset is the latest setting for the talents of Inspector Ian Rutledge, a veteran of the First World War, and still haunted - literally - by his actions. Indeed, his personal ghost only serves to complicate things as his inner doubts blend in to the trauma of the case. The disappearance of two children, the murder of a woman supposed to be their mother, and an unstable suspect who may or may not be guilty form the bones of Todd's latest psychological thriller, augmented by the in-depth and impressive character analysis that distinguishes his novels.